Cannabidiol modulates brain molecular alterations, gut microbiota dysbiosis and alcohol self-administration in a mouse model of fetal alcohol spectrum disorder - Navarrete F.; Cabrera-Rubio R.; Gasparyan A.; Aarnio R.; López-Picón F.; Helin S.; Rajander J.; Collado M.C.; Manzanares J. (Elsevier BV, 2026)
Fetal Alcohol Spectrum Disorder (FASD) is a range of neurodevelopmental abnormalities caused by Perinatal Alcohol Exposure (PAE), leading to profound behavioral and molecular disturbances in the offspring. Unraveling the central and peripheral mechanisms involved, including the microbiota-gut-brain axis, is crucial to improving our understanding of the disease and developing new treatment strategies from a sex perspective. In this study, we investigated the impact of PAE on emotional behavior, brain biomarkers, and gut microbiota composition and diversity in a preclinical C57BL/6 J mouse model, as well as the extent of their vulnerability to alcohol consumption. Furthermore, we have also explored the potential modulatory effects of cannabidiol (CBD) administered chronically (30 mg/kg/day, i.p.) from weaning on PAE-induced sex-dependent emotional and brain molecular impairments, gut microbiota dysbiosis, and increased alcohol reinforcing and motivational actions. FASD model mice showed increased anxiety- and depressive-like behavior accompanied by sex-dependent changes in synaptic density, dopamine D2/D3 receptors availability, cannabinoid receptors 1 and 2 (Cnr1/Cnr2), tyrosine hydroxylase (Th), and serotonin transporter (Slc6a4) gene expression, and gut microbiota dysbiosis. Interestingly, CBD sex-dependently improved and/or normalized PAE-induced behavioral and molecular disturbances. In addition, females but not males exposed to the animal model of FASD showed a higher motivation to drink alcohol, which CBD abolished. Our findings provide new insights into the brain and gut microbiota sex-dependent mechanisms involved in FASD pathophysiology and further highlight the therapeutic potential of CBD to improve the management of FASD-induced emotional disturbances and alcohol addiction from a sex-oriented approach.